The association between place of residence and infant and child mortality in Angola - Mathekga, Jacob Kgaogelo (My University, 2015)
Angola continues to experience some of the highest infant and child mortality rates in Africa. Socio-economic conditions in rural areas (which were worse affected by the civil war) are reported to be poorer as compared to urban areas. The study aims to examine the effects of type of place of residence on infant and child mortality in Angola. Methodology: Cox Hazard method was used to analyze the 2011 Angola Malaria Indicators Survey (AMIS) data using the STATA 12 program. Type of place of residence is used as a key variable for the study. Descriptive analyses were conducted to examine the levels of infant and child mortality in urban and rural areas as well as by other characteristics. Results and conclusion: The study finds that there is no relationship between type of place of residence and infant and child mortality, while being born a girl reduces the chances of infant mortality. Being born in the second and third order and being born from a mother aged 25 – 34 years increases the child’s mortality chances. Big households have a positive effect in reducing both infant and child mortality in Angola. The findings of the study open more questions for further exploration on the topic on factors determining infant and child mortality.
DEPARTMENT OF DEMOGRAPHY AND POPULATION STUDIES SCHOOL OF SOCIAL SCIENCES FACULTY OF HUMANITIES UNIVERSITY OF THE WITWATERSRAND 17 June 2014